SALIVARY GLUCOSE CONCENTRATION IN TYPE-II DIABETIC PEOPLE: A CASE–CONTROL STUDY: ABSTARCT, Introduction, Materials and Methods, Result and Discussion, conclusion, Reference - NIRMALA A; MAZHER SULTANA; SHARON NS (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the present study was to find a non-invasive method of sample collection that can be used to diagnose and monitor diabetes mellitus (DM). Methods: In this study, saliva as a diagnostic fluid was collected noninvasively from subjects with modest training and this offers a cost-effective method for screening diabetes. To evaluate the association of blood glucose level with salivary glucose in Type-II diabetic (Type-II D) patients, a case– control study was conducted on 200 test and 200 healthy control people in selected study village in Kanchipuram (District). The glucose level was measured in saliva and blood plasma by glucose oxidase and peroxidase method. Results: A highly significant positive correlation between fasting salivary glucose (69.377±14.329 mg/dl) and plasma glucose (249.935±64.65 mg/dl) in diabetic patients and in control group, plasma glucose level 117.545±10.595 and saliva glucose level 49.271±13.795 mg/dl was observed. Conclusion: From this study, it can be concluded that fasting salivary glucose level can be used as a non-invasive diagnostic, as well as monitoring tool to assess the glycemic status of Type-II DM patients.